Transcriptomic analysis in pediatric spinal ependymoma reveals distinct molecular signatures - Lourdusamy, Anbarasu; Luo, Li Z.; Storer, Lisa CD.; Cohen, Kenneth J.; Resar, Linda; Grundy, Richard G. (Impact Journals, 2017)
Pediatric spinal ependymomas (SEPN) are important albeit uncommon malignant central nervous system tumors with limited treatment options. Our current knowledge about the underlying biology of these tumors is limited due to their rarity. To begin to elucidate molecular mechanisms that give rise to pediatric SEPN, we compared the transcriptomic landscape of SEPNs to that of intracranial ependymomas using genome-wide mRNA and microRNA (miRNA) expression profiling in primary tumour samples. We found that pediatric SEPNs are characterized by increased expression of genes involved in developmental processes, oxidative phosphorylation, cellular respiration, electron transport chain, and cofactor metabolic process. Next, we compared pediatric spinal and intracranial ependymomas with the same tumours in adults and found a relatively low number of genes in pediatric tumours that were shared with adult tumours (12.5%). In contrast to adult SEPN, down-regulated genes in pediatric SEPN were not enriched for position on chromosome 22. At the miRNA level, we found ten miRNAs that were perturbed in pediatric SEPN and we identified regulatory relationships between these miRNAs and their putative targets mRNAs using the integrative miRNA-mRNA network and predicted miRNA target analysis. These miRNAs include the oncomiR hsa-miR-10b and its family member hsa-miR-10a, both of which are upregulated and target chromatin modification genes that are down regulated in pediatric SEPN. The tumor suppressor, hsa-miR-124, was down regulated in pediatric SEPN and it normally represses genes involved in cell-cell communication and metabolic processes. Together, our findings suggest that pediatric SEPN is characterized by a distinct transcriptional landscape from that of pediatric intracranial EPNs or adult tumors (both SEPNs and intracranial EPNs). Although confirmatory studies are needed, our study reveals novel molecular pathways that may drive tumorigenesis and could serve as biomarkers or rational therapeutic targets.